A new POLH mutation in a consanguineous Chinese family with xeroderma pigmentosum variant type. (19th August 2022) - OuYang, Xiaoliang; Zhang, Deng; Wang, Xiuping; Yu, Simin; Xiao, Zhen; Li, Chunming
Abstract : We report a Chinese consanguineous family with a variant type of xeroderma pigmentosum (XPV), and identified one novel mutation in the patient. Our study expands the mutational spectrum of XPV. Click here for the corresponding questions to this CME article.